2021
DOI: 10.1111/jfpp.16113
|View full text |Cite
|
Sign up to set email alerts
|

Saponin‐rich fractions from Codonopsis javanica root extract and their in vitro antioxidant and anti‐enzymatic efficacy

Abstract: Saponins are complicated compounds made up of sugars linked to a triterpenoid, steroid, or steroidal alkaloid that are widely distributed in plant kingdoms, especially in ginseng species (Cheok

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…(2016) with some modifications as described by Do et al . (2021), where allopurinol served as a positive standard. The samples (whole extract and its fractions) and the standard were prepared at concentrations ranging from 50 to 500 μg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) with some modifications as described by Do et al . (2021), where allopurinol served as a positive standard. The samples (whole extract and its fractions) and the standard were prepared at concentrations ranging from 50 to 500 μg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The XO inhibitory efficacy was spectrophotometrically assayed at 295 nm. The percentage inhibition of XO was calculated as follows (Do et al., 2021):%XOinhibition=italicAitalicCitalicAitalicSAC×100where Ac is the absorption of the control and As is the absorption of the test sample.…”
Section: Methodsmentioning
confidence: 99%
“…high fat emulsion 3 . It has been reported that three different doses of polysaccharide obtained from C. pilosula (100, 200 and 300 mg/kg/d) effectively decreased blood glucose and insulin in serum, enhance SOD activity and reduce the content of MDA in serum of mice 105 . Based on these reports, it was considered to have significant hypoglycemic effect in diabetic mice by improving insulin resistance 106,107 .…”
Section: Pharmacologymentioning
confidence: 99%